2020
DOI: 10.1002/path.5530
|View full text |Cite
|
Sign up to set email alerts
|

ZHX2 inhibits SREBP1c‐mediated de novo lipogenesis in hepatocellular carcinoma via miR‐24‐3p

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. Lipogenesis has been considered as a critical player in HCC initiation and progression. However, the underlying mechanism is still not fully understood. Here, we identified zinc fingers and homeoboxes 2 (ZHX2), an HCC-associated tumor suppressor, as an important repressor of de novo lipogenesis. Ectopic expression of ZHX2 significantly inhibited de novo lipogenesis in HCC cells and decreased expression of FASN, ACL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Previous studies using hepatoma cell lines indicated that increased Zhx2 expression resulted in reduced cell proliferation in vitro and reduced xenograft growth in nude mice [ 21 ] and that HTVI of oncogenes AKT/Myc led to more tumors in Zhx2 liver‐knockout mice, [ 22 ] consistent with Zhx2 functioning as a tumor suppressor. To explore the role of Zhx2 in the initiation and progression of tumor development in vivo , we used the well‐established DEN model in Zhx2 wt and Zhx2 KO mice.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies using hepatoma cell lines indicated that increased Zhx2 expression resulted in reduced cell proliferation in vitro and reduced xenograft growth in nude mice [ 21 ] and that HTVI of oncogenes AKT/Myc led to more tumors in Zhx2 liver‐knockout mice, [ 22 ] consistent with Zhx2 functioning as a tumor suppressor. To explore the role of Zhx2 in the initiation and progression of tumor development in vivo , we used the well‐established DEN model in Zhx2 wt and Zhx2 KO mice.…”
Section: Resultsmentioning
confidence: 84%
“…[ 19 , 20 ] Tissue culture and xenograft studies using human hepatoma cell lines indicated that Zhx2 inhibits cell proliferation and reduces levels of cyclins A and E, [ 21 ] supporting the possibility that Zhx2 functions as a tumor suppressor. Liver‐specific Zhx2 knockout mice had increased tumors compared with wild‐type controls after hydrodynamic tail‐vein injection (HTVI) of the oncogenes AKT and Myc, [ 22 ] consistent with tumor suppressor activity of Zhx2.…”
Section: Introductionmentioning
confidence: 94%
“…As an HCC-associated tumor suppressor, zinc fingers and homeoboxes 2 (ZHX2) is negatively associated with SREBP-1c in HCC cell lines and human specimens. ZHX2 can increase miRNA-24-3p at the transcription level to induce SREBP-1c degradation for the suppression of HCC progression ( 94 ). A member of the acyl-CoA synthetase (ACS) family, acyl CoA synthetase 4 (ACSL4) has been identified as an oncogene and a novel marker of alpha-fetoprotein-high subtype HCC.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…SREBP-1 is a transcriptional factor and plays a pivotal role in the proliferation and metastasis of liver cancer cells by regulating fatty acid synthesis and [81] and suppressing liver inflammation [82]. Other factors, such as long-chain acyl CoA synthetase 4 (ACSL4) [83], caveolin-1 (Cav1) [84], and zinc fingers and homeoboxes 2 (ZHX2) [85], can regulate lipid metabolism via the SREBP1 signaling pathway. Lipid metabolism is correlated tightly with glucose metabolism in HCC.…”
Section: Srebp-1mentioning
confidence: 99%